2012
DOI: 10.1002/ajmg.a.35634
|View full text |Cite
|
Sign up to set email alerts
|

Three polymorphisms in IRF6 and 8q24 are associated with nonsyndromic cleft lip with or without cleft palate: Evidence from 20 studies

Abstract: Nonsyndromic cleft lip with or without cleft palate (NSCL/P) is one of the most common craniofacial malformation in humans. Three polymorphisms, rs2235371 and rs642961 in interferon regulatory factor 6 (IRF6), rs987525 on 8q24, have been shown to be associated with NSCL/P risk in several studies. However, the magnitudes of the association varied between studies. We therefore performed a meta-analysis to investigate this relationship. Two authors independently extracted information on the characteristics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 39 publications
(54 reference statements)
3
26
0
Order By: Relevance
“…Our findings are consistent with previous human GWAS studies (Birnbaum et al, 2009b;Grant et al, 2009;Beaty et al, 2010;Ludwig et al, 2012). In addition, our findings are also consistent with the previous meta-analysis of genetic association studies by Wang et al (2012), that included 10, 6, and 8 studies in the pooling of rs2235371 and rs642961 for IRF6, and rs987525 for 8q24, respectively. We confirmed the previous findings by expanding to a larger number of included genetic association studies (i.e., 15, 11, and 12 studies for these corresponding polymorphisms) and applying Bonferroni correction for multiple tests.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with previous human GWAS studies (Birnbaum et al, 2009b;Grant et al, 2009;Beaty et al, 2010;Ludwig et al, 2012). In addition, our findings are also consistent with the previous meta-analysis of genetic association studies by Wang et al (2012), that included 10, 6, and 8 studies in the pooling of rs2235371 and rs642961 for IRF6, and rs987525 for 8q24, respectively. We confirmed the previous findings by expanding to a larger number of included genetic association studies (i.e., 15, 11, and 12 studies for these corresponding polymorphisms) and applying Bonferroni correction for multiple tests.…”
Section: Discussionsupporting
confidence: 93%
“…4 Indeed, interferon regulatory factor 6 (IRF6) gene and the 8q24 region are the most reliable genetic risk factors for NSCLAEP and have been validated in different populations. 5,6 In previous studies, we have investigated the association of several GWAS-susceptibility signals in the Brazilian population, confirming some associations, including 8q24 region, and failing to confirm others, such as IRF6, most probably due to differential frequencies of the risk alleles which are dependent upon ethnicity. [7][8][9][10][11][12][13] Two recent well-designed GWAS on NSCLAEP have been conducted.…”
mentioning
confidence: 89%
“…Previous studies based on genome‐wide screening (mainly genome‐wide association studies‐GWAS) have identified several NSCL±P risk genes and chromosomal regions, but few have shown consistent replication across different populations . Indeed, interferon regulatory factor 6 ( IRF6 ) gene and the 8q24 region are the most reliable genetic risk factors for NSCL±P and have been validated in different populations . In previous studies, we have investigated the association of several GWAS‐susceptibility signals in the Brazilian population, confirming some associations, including 8q24 region, and failing to confirm others, such as IRF6 , most probably due to differential frequencies of the risk alleles which are dependent upon ethnicity .…”
Section: Introductionmentioning
confidence: 99%
“…This is clearly exemplified in interferon regulatory factor 6 ( IRF6 ) and 8q24 locus, the most reliable genetic factors for NOC (Beaty, Marazita, & Leslie, ; Dixon et al, ). Differences in the prevalence of IRF6 rs2235371 and 8q24 rs987525 alleles among Caucasians and Asians are observed, resulting in distinct effects on NOC susceptibility (Wang, Pan, Zhang, & Wang, ). While IRF6 rs2235371 showed a protective effect among Asians, with no effects in Caucasians, 8q24 rs987525 increased the risk for NOC among Caucasians but not among Asians (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the prevalence of IRF6 rs2235371 and 8q24 rs987525 alleles among Caucasians and Asians are observed, resulting in distinct effects on NOC susceptibility (Wang, Pan, Zhang, & Wang, ). While IRF6 rs2235371 showed a protective effect among Asians, with no effects in Caucasians, 8q24 rs987525 increased the risk for NOC among Caucasians but not among Asians (Wang et al, ). The effects of bone morphogenetic protein 4 ( BMP4 ) gene are also influenced by ethnicity, since the C allele of BMP4 rs17563 is a risk factor for NOC in Asians and Caucasians, but demonstrates a protective effect in the Brazilian population (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%